2015 American Control Conference (ACC) 2015
DOI: 10.1109/acc.2015.7171915
|View full text |Cite
|
Sign up to set email alerts
|

Neurocontrol: Methods, models and technologies for manipulating dynamics in the brain

Abstract: This paper accompanies a tutorial session at the 2015 American Control Conference, and provides a survey of emerging technologies and research problems at the boundary between systems engineering, neuroscience and neural medicine. Emphasis will be placed on both recent theoretical developments -for example, system identification and controllability in neuronal networks -and real-world constraints in applications such as clinical deep brain stimulation, or optical stimulation in experimental neuroscience. Discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 166 publications
(141 reference statements)
0
11
0
Order By: Relevance
“…Should the reader instead be searching for an excellent treatment of various control methods for single neurons or for ensembles of neurons, we direct them to the recent textbook by Schiff (2012), and to references therein. For further details on emerging control technologies in the brainespecially invasive electrical and optical stimulation at rapid timescales (milliseconds or below)-and associated modelling approaches, please see the recent review by Ritt and Ching (2015).…”
mentioning
confidence: 99%
“…Should the reader instead be searching for an excellent treatment of various control methods for single neurons or for ensembles of neurons, we direct them to the recent textbook by Schiff (2012), and to references therein. For further details on emerging control technologies in the brainespecially invasive electrical and optical stimulation at rapid timescales (milliseconds or below)-and associated modelling approaches, please see the recent review by Ritt and Ching (2015).…”
mentioning
confidence: 99%
“…Model predictive control has been applied to Parkinson's disease (PD) using an extended autoregressive model [27], and various forms of delayed feedback have also been investigated [28,29]. Further review can be found for instance in [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…with electrical stimulation, Histed et al, 2009) or populations of neurons are uniformly stimulated to enhance or suppress activity (e.g. with optogenetic stimulation; Cardin et al, 2010;Ritt and Ching, 2015). In contrast, neural representations are diverse and are distributed across the population.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, control of neural systems has been successful when the structure of the system is well mapped (Ahmadian et al, 2011;Li et al, 2013), such as controlling the specific neurons responsible for locomotion in C. elegans (Yan et al, 2017). However, controlling complex systems, such as large-scale neural populations, is poorly understood (Ritt and Ching, 2015;Tang and Bassett, 2018).…”
Section: Introductionmentioning
confidence: 99%